Subculture and Etiolation Treatment Promotes Rooting Ability of Upper Branches of Black Locust Crown - Jie Zhang; Ye Zhao; Anan Duan; Wei Wang; Yuhan Sun; Li Dong; Sen Cao; Xiuyu Li; Xiaodi Liu; Chao Han; Saleem Uddin; Wei Bi; et al. (Forest Science, 2023)
The black locust (Robinia pseudoacacia L.) is an economically and ecologically important tree worldwide. However, maturation and position effects affect its asexual reproduction. Despite etiolation treatment and successive subcultures promoting the plant cutting’s rooting rate, whether the promoting effects of aging (upper) branches and young (lower) branches are consistent is unknown. Therefore, we evaluated the relevant rooting ability indicators of tree age effect and its location effect in 26-year-old R. pseudoacacia trees and the current-year branches of different parts. Branches of the upper and lower parts of these trees underwent accelerated germination to generate shoots as explants. We subjected the tissue culture–generated shoots to an etiolation treatment to investigate how the treatment and subculture time affected the rooting ability of the shoot explants induced by different parts of the black locust branch. Tissue culture shoots subjected to the etiolation treatment exhibited a 2–3 day shorter rooting time. Shoots from the upper crown organs achieved a rejuvenation effect, which manifested as enhanced rooting capacity. Our study results provide a theoretical basis for maintaining the juvenility and consistency of clones. Besides having theoretical and practical value, our study also guides the selection of suitable propagation materials for production.

Spatial Patterns in Baseflow Mean Response Time across a Watershed in the Loess Plateau: Linkage with Land-Use Types - Xu-dong Huang; Dong Wang; Pei-pei Han; Wen-chuan Wang; Qing-jie Li; Xiao-li Zhang; Ming-wei Ma; Bao-jian Li; Shi-jie Han (Forest Science, 2020)
Understanding the relation between land-use types and baseflow mean response time (BMRT) is important to explore the response mechanism of baseflow processes in watersheds. BMRT was determined using an instantaneous unit hydrograph. The instantaneous unit hydrograph parameters were estimated by autocorrelation functions. The relative importance of land-use types in determining BMRT dynamics was assessed by hydrological model and partial least-squares regression. Our study suggests greater effects of urban area on BMRT than the effects of forest and agricultural land. This may be because the urban interception impervious area may impede baseflow generation over a short timescale. The effects of agricultural land are greater than those of forest in areas with steeper hillslopes, but lower than those of the forest in areas with more plains, reflecting the varied ability of forest and agricultural lands with different topography to hinder overland flow. Variations of BMRT are strongly linked to land use in the watershed. Overall, our study provides insight into the BMRT and dominant factors of land-use types in watersheds, planning of sustainable water resource use, and ecological protection in watersheds.

Litterfall Dynamics of an Evergreen Broadleaf Forest and a Pine Forest in the Subtropical Region of China - Zhi An Li; Bi Zou; Han-ping Xia; Hai Ren; Jiang-ming Mo; Hong Weng (Forest Science, 2005)
Monthly litterfall was monitored over a 10-year period from an evergreen broadleaf forest (EBF) and a pine forest (PF) in subtropical South China. During this period, litter was also collected bimonthly from the forest floor for 2 years. Total annual litterfall in EBF fluctuated around 9 Mg ha−1 with leaves, branches, and miscellanea accounting for 52.5%, 22.2%, and 25.3%, respectively. Total annual litterfall alternated between high and low values in consecutive years. Storms and pest outbreaks were responsible for most of the peaks in both monthly and annual litterfall. Litter from each of 43 species was recorded, but 9 species contributed about 85% of total litterfall. Dominant species shed their leaves in a more regular pattern with peaks mainly from Jan. to Mar. Pine forest (Pinus massoniana) produced much less litterfall than EBF, with a mean of 2.7 Mg ha−1. Here, leaves accounted for 73.2% of total litterfall, branches only 11.4%, and miscellanea 15.4%. Litter on the ground amounted to 5.2 Mg ha−1 in EBF and 2.9 Mg ha−1 in PF. The results show that this climax forest has much higher litterfall and forest floor mass than the pine forest, and litterfall is rather stable with regard to annual variation. FOR. SCI. 51(6):608–615.